Workshop Pembuatan Video Animasi sebagai Media Penyuluhan Kesehatan Masyarakat di Masa New Normal - Nur Fadhilah Arifin; Risnayanti Anas; Nur Rahmah (Idea Pengabdian Masyarakat, 2022)
The emergence of the Industrial Revolution 4.0 caused changes in various sectors, including the world of health. The Covid-19 pandemic or Corona virus disease has changed the world order. In order to prevent the further spread of the corona virus, adjustments have been made in various work sectors. Everything that requires face-to-face services is turned into online services. Health instructors in the new normal are required to be able to innovate in accordance with the 4.0 industrial revolution in digital health promotion. One form of media that is often used is video media. Video media relies on the sense of sight and the sense of hearing to visualize certain information so that efforts to convey this information are more effective and with this video media can be used as a tool to deliver health education to the general public. This animated video was chosen because this animated video is considered more interesting and easily understood by the public. For this reason, it is very necessary for health workers and cadres to be given training on how to make animated videos as a media for counseling in the new normal period.